1989
DOI: 10.1002/jcp.1041390307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biaxial deformation on pulmonary artery endothelial cells

Abstract: An apparatus has been designed to subject vascular cells grown on a compliant substrate in vitro to uniform, quantifiable levels of biaxial deformation. The system described can be controlled with respect to strain level, rate, and frequency to mimic the pulsatile force to which vascular cells are exposed in vivo under both physiologic and pathologic conditions. In the experiments presented here, bovine pulmonary artery endothelial cells were grown on a substrate of segmented polyurethane urea (Mitrathane). Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…The cells were grown on a type I collagen-coated silicon membrane (Specialty Manufacturing, Saginaw, MI). Mechanical deformation of the cells was performed using a Tensorcell III, a device designed to apply precise and reproducible biaxial strains (supplied by CT Group, Crested Butte, CO) to the membrane on which the cells were grown (18). It has previously been shown that the cells experience essentially the same deformations as the substrate on which they are grown (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were grown on a type I collagen-coated silicon membrane (Specialty Manufacturing, Saginaw, MI). Mechanical deformation of the cells was performed using a Tensorcell III, a device designed to apply precise and reproducible biaxial strains (supplied by CT Group, Crested Butte, CO) to the membrane on which the cells were grown (18). It has previously been shown that the cells experience essentially the same deformations as the substrate on which they are grown (5).…”
Section: Methodsmentioning
confidence: 99%
“…For experimental wells, biaxial strain was applied by stretching the elastic membrane cyclically for 24 and 48 h to provide 2.5% strain. Details of the strain level estimation, the design of the Tensor stretch instrument, and computer program are based on published data (18,48). The strain level of 2.5% was used in this study because this condition was found to be sufficient to produce molecular changes without inducing apparent cell injury (12).…”
Section: Methodsmentioning
confidence: 99%
“…V ascular M edicine 2004; 9: [35][36][37][38][39][40][41][42][43][44][45] portion of a vessel. 40 Regions proximal to and in the throat of the stenosis experienced time-averaged, uniform normal and high shear, respectively, while immediately distal to the stenosis, complex, non-uniform ow patterns that included ow separation, stagnation points, low laminar ow and eddy currents were observed.…”
Section: Figurementioning
confidence: 99%
“…144,145 In fact, the expression of IL1R L1 and TN F receptorassociated factor-3 (TRAF -3), two LSS-upregulated genes, has been implicated in the inhibition of Toll-like receptors (TLR4 and TLR1) and CD40, respectively, two signaling pathways implicated in in ammation and atherosclerosis. 59,145 V ascular M edicine 2004; 9: [35][36][37][38][39][40][41][42][43][44][45] Endothelial differentiation induced by LSS: sculpting the phenotypic response It has been hypothesized that uid ow acts as a differentiative stimuli to modulate endothelial phenotype=function. This hypothesis can be viewed on two levels.…”
Section: The Mitigation Of Oxidant Stress and In Ammation By Lssmentioning
confidence: 99%
See 1 more Smart Citation